2, 4 and 2, 5-bis(benzooxazol-2′-yl)hydroquinone (DHBO) and their borate complexes: synthesis and optical properties. (5th May 2016) - Benelhadj, Karima; Massue, Julien; Ulrich, Gilles
Abstract : 2, 4 and 2, 5-bis(benzooxazol-2′-yl)hydroquinone (DHBO) scaffolds show fluorescence stemming from an ESIPT process but also act as chelates toward boron fragments. Abstract : This article describes the multistep synthesis and the solution/solid-state optical properties of a series of highly fluorescent dyes based on either a 2, 4 or a 2, 5-bis(benzooxazol-2′-yl)hydroquinone (DHBO) scaffold. Their fluorescence emission stems from an intrinsic excited-state intramolecular proton transfer (ESIPT) photophysical process, which is highly dependent on the environment of the probe (solvent/matrix). Besides their ESIPT emission, these dyes are also excellent chelates towards boron(iii ) fragments such as BF2 or B(Ar)2 leading to singlet emitters with a quantum yield in solution reaching up to 51%. The solid-state emission of all these fluorophores was investigated by dispersing them as pellets in a KBr matrix revealing an intense emission in condensed matter.